Internalization of 'Panca Jiwa Pondok' in Pesantren: An Ethnomethodological Study - Nurul Fitriyah A.W; Rahmatullah, Azam Syukur; Othman, Mohd Sukki (Jurnal Pendidikan Islam, 2023)
Purpose – This research aims to explore a deep understanding of the internalization of the five principles of the Pesantren among all stakeholders, especially the students. Another goal is to explore the essence and implementation of the Panca Jiwa Pondok of the Pesantren that have been initiated by the founders of Pondok Pesantren Gontor in Ponorogo, East Java, and how Gontor alums and non-alumni boarding schools adopt this. Design/methods/approach – This research uses a qualitative method with an ethnomethodological approach. This method focuses on the resources, procedures, and practices that group or community members use to produce and recognize social realities that can be sensed. The research was conducted at Al Kamal Islamic Boarding School in Tambaksari Kuwarasan, Kebumen, Indonesia. Data was collected through natural interviews in daily life involving researchers in the pesantren environment. The data analysis process was conducted descriptively since the first data collection, so it did not wait for excessive data accumulation. Findings – This research reveals three main characteristics of the Panca Jiwa Pondok: strengthening of social piety, strengthening of intrapersonal aspects, and spirituality. The internalization process of "Panca Jiwa Pondok" to the students through stages: introduction, thinking, imitation, and internalization, as well as interpretation. Research implications – The findings of this study have important implications for educational institutions, both general and Islamic-based, regarding the implementation and strengthening of the five principles of the Pesantren in teaching and learning activities. This is expected to help students or students understand the essence of learning so that they can grow into individuals with strong character as learners.